“Moving from place to face”:: Landscape and Longing in the Poetry of John Barton - May, Robert (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
John Barton's poetry constantly considers how Canada's national ambivalence towards the landscape can be expressive of an equally pervasive sexual dissidence, particularly for those who diverge from the heteronormative tradition. Echoing Peter Dickinson's Here is Queer, Barton conceives of homosexuality in nationalistic terms; he uses the Canadian landscape to articulate the gay experience, just as earlier writers had used it to attempt to communicate an authentic Canadian experience. In early works like A Poor Photographer (1981) and West of Darkness (1987), Barton uses the sky, sea, and trees as images of alienation from society. In Great Men (1990) and later poetry, they become symbols of broadened horizons and the ability to see past culturally prescribed roles. This change in symbolic significance is just one manifestation of the way in which Barton anchors his exploration of homosexual identity in landscape imagery.